2019
DOI: 10.1177/2059204318816066
|View full text |Cite|
|
Sign up to set email alerts
|

Musical Style Affects the Strength of Harmonic Expectancy

Abstract: Research in music perception has typically focused on common-practice music (tonal music from the Western European tradition, ca. 1750-1900) as a model of Western musical structure. However, recent research indicates that different styles within Western tonal music may follow distinct harmonic syntaxes. The current study investigated whether listeners can adapt their harmonic expectations when listening to different musical styles. In two experiments, listeners were presented with short musical excerpts that p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…This approach might allow richer investigations of music and culture than exist within the framework of traditionally conceived ''cross-cultural'' work. For example, musicians in a city like New York may participate in multiple subcultures actively playing genres such as classical music, jazz, punk rock, and electronic noise music, and listeners adapt their harmonic expectations to the style at hand (Vuvan & Hughes, 2019). Similarly, within the same ethnically diverse city it can be possible to identify groups of individuals whose exposure to particular musical structures (e.g., Afro-Cuban rhythm) can occur over a lifetime of listening and dancing, through explicit instruction in a college music course, incidental exposure in clubs or on the radio, or not at all (Getz, Barton, & Kubovy, 2014).…”
Section: Culture(s): Recommendationsmentioning
confidence: 99%
“…This approach might allow richer investigations of music and culture than exist within the framework of traditionally conceived ''cross-cultural'' work. For example, musicians in a city like New York may participate in multiple subcultures actively playing genres such as classical music, jazz, punk rock, and electronic noise music, and listeners adapt their harmonic expectations to the style at hand (Vuvan & Hughes, 2019). Similarly, within the same ethnically diverse city it can be possible to identify groups of individuals whose exposure to particular musical structures (e.g., Afro-Cuban rhythm) can occur over a lifetime of listening and dancing, through explicit instruction in a college music course, incidental exposure in clubs or on the radio, or not at all (Getz, Barton, & Kubovy, 2014).…”
Section: Culture(s): Recommendationsmentioning
confidence: 99%
“…While de Clercq's argument stems from a perspective of music analysis rather than perception, it nevertheless supports the notion that representations of the metrical hierarchy should be style-specific. More generally, our findings suggest that listeners are keenly aware of musical style, and that style should thus be an Running Head: BACKBEAT PLACEMENT AFFECTS TEMPO JUDGMENTS 20 important factor for general theories of music cognition; a claim further supported by a growing body of research (Gjerdingen & Perrott, 2008;Vuvan & Hughes, 2019).…”
Section: Discussionmentioning
confidence: 51%
“…Is it possible that stylespecific parameters might have such an impact? Listeners are keenly aware of stylistic traits that define musical genres (Gjerdingen & Perrott, 2008), and this has been shown to impact listeners' expectations of harmony (Vuvan & Hughes, 2019) ). If the backbeat cycle is something to which most listeners entrain, it follows that any change in the rate of that cycle, such as the case of half or double time, could affect the listeners' overall perception of tempo.…”
Section: Backbeat and Tempo Perceptionmentioning
confidence: 99%
“…Moreover, listeners' style-specific representations can be evoked using a simple timbral cue, as the classical and rock excerpts were identical except for the instrument they employed. In previous work Vuvan and Hughes (2019) demonstrated that reducing the number of style cues available to listeners weakens the distinction between tonal representations for classical and rock. Thus, in the current experiment, the successful instantiation of distinct tonal hierarchies for classical and rock with minimal stylistic manipulation is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Craton et al (2016Craton et al ( , 2019 have reported that participants show preferences for chords found to be common in the rock corpora, but their studies did not include comparing participant responses to ecologically valid stimuli in both the classical and rock contexts. Recently, we reported the results of an experiment in which participants heard a timbre-based style prime (Classical or Rock), followed by either a bVII-I or a V-I cadence (Vuvan & Hughes, 2019). Participants were required to rate the cadence in terms of how well it fit with the prime.…”
Section: Probe Tone Paradigm Reveals Less Differentiated Tonal Hierarchy In Rock Musicmentioning
confidence: 99%